Solihabitans fulvus gen. nov., sp. nov., a member of the family Pseudonocardiaceae isolated from soil. Issue 2 (25th February 2022) - Jin, Chun-Zhi; Jin, Long; Liu, Min-Jiao; Lee, Jong-Min; Park, Dong-Jin; Kim, Chang-Jin
Abstract : A polyphasic taxonomic study was carried out on an actinobacterial strain (AN110305 T ) isolated from soil sampled in the Republic of Korea. Cells of the strain were Gram-stain-positive, aerobic, non-motile and rod-shaped. Comparative 16S rRNA gene sequence studies showed a clear affiliation of strain AN110305 T with Actinomycetia, with highest pairwise sequence similarities to Goodfellowiella coeruleoviolacea DSM 43935 T (97.6%), Umezawaea tangerina MK27-91F2 T (97.0%), Kutzneria chonburiensis NBRC 110610 T (96.9%), Kutzneria buriramensis A-T 1846 T (96.8%), Umezawaea endophytica YIM 2047X T (96.8%), Kutzneria albida NRRL B-24060 T (96.7%) and Saccharothrix coeruleofusca NRRL B-16115 T (96.6%). Cells of strain AN110305 T formed pale-yellow colonies on Reasoner's 2A agar. MK-9 (H4 ) (68%) and MK-10 (H4 ) (32%) were the predominant menaquinones. Diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylmethyl ethanolamine, hydroxy-phosphatidylethanolamine, an unidentified aminolipid and an unidentified aminophospholipid were major polar lipids. Iso-C16:0 (24.5%), anteiso-C15:0 (19.3%), anteiso-C17:0 (15.7%) and iso-C15:0 (15.2%) were the major fatty acids and meso -diaminopimelic acid was the pepdidoglycan. The cell-wall sugars were composed of galactose, glucose, mannose and ribose. The genomic DNA G+C content was 70.7 mol%. Based on genotypic and phenotypic data, strain AN110305 T could be distinguished from all genera within the family Pseudonocardiaceae and represents a novel genus and species named Solihabitans fulvus gen. nov., sp nov. The type strain is AN110305 T (=KCTC 39307 T =DSM 103572 T ).